Bioinformatic-based approach for mutagenesis of plant immune Tm-22 receptor to confer resistance against tomato brown rugose fruit virus (ToBRFV) - Rivera-Márquez, Karla; Núñez-Muñoz, Leandro Alberto; Calderón-Pérez, Berenice; De La Torre-Almaraz, Rodolfo; Vargas-Hernández, Brenda Yazmín; Ruiz-Medrano, Roberto; Xoconostle-Cázares, Beatriz (Frontiers in Plant Science, 2022)
Nucleotide-binding leucine-rich repeat (NLR) plant immune receptors mediate the recognition and activation of defense signaling pathways in response to intra- and extracellular pathogens. Several NLR such as Tm-1, Tm-2, and Tm-22 have been introgressed into commercial solanaceous varieties to confer protection against different tobamoviruses. Particularly, Tm-22 was used during recent decades to confer resistance against Tobacco mosaic virus, Tomato mottle mosaic virus and Tomato mosaic virus, which recognizes the viral movement protein (MP). However, Tomato brown rugose fruit virus (ToBRFV), a novel tobamovirus, can avoid the protection conferred by Tm-22 due to the presence of key amino acid substitutions in the MP. The aim of this work was to identify key residues involved in the interaction between Tm-22 and ToBRFV MP through bioinformatic analyses, and to identify potential Tm-22 mutations that could generate higher binding affinity. In silico 3D structure prediction, molecular docking and computational affinity methods were performed. We predicted that R350, H384 and K385 Tm-22 residues are relevant for the interaction with MP, and two mutations (H384W and K385L) were identified as putative sites to increase the affinity of Tm-22 to the MP with the potential elicitation of resistance against ToBRFV.